Ing-Nouns as a Type of Processual Lexicon: Addressing Issue of Recent Borrowings in Russian - N. E. Petrova; G. S. Samoylova (Научный диалог)
This study explores the processual properties of recent borrowed nouns featuring the component -ing-, characterized in this article as a suffix with distinct structural and semantic features. The objective of the research is to delineate various semantic groups of “ingnouns” based on their contextual paradigmatic and syntagmatic relationships, particularly regarding their verbal-nominal functional properties. The material for this analysis is derived from the subcorpora “Social Networks” and “Central Mass Media” of the Russian National Corpus. It is demonstrated that the processual nature of “ing-nouns” is significantly influenced by their form, with bilingualism among Russian speakers identified as a contributing factor to the development of processuality. The processual interpretation of “ing-nouns” is evidenced by the interpretations of their lexical meanings, which reflect the linguistic reflections of speakers, as well as the introduction of the term “process” into the text. Among the verbal syntagmatic connections of “ingnouns,” the governance of the genitive case form with either object or subject meanings is noted, alongside the explication of action manner semantics through association with instrumental case forms or lexemes such as method and mechanism. The active nature of metonymic semantic derivation based on the processual meanings of “ing-nouns” is confirmed.